Correction: Pd-Catalysed [3 + 2]-cycloaddition towards the generation of bioactive bis-heterocycles/identification of COX-2 inhibitors via in silico analysis. Issue 46 (17th November 2022) - Sathish, Elagandhula; Sharma, Manmohan; Ansari, Arshad J.; Joshi, Gaurav; Pandit, Akansha; Shukla, Monika; Kumari, Neha; Sharon, Ashoke; Verma, Ved Prakash; Sawant, Devesh M.
Abstract : Correction for 'Pd-Catalysed [3 + 2]-cycloaddition towards the generation of bioactive bis-heterocycles/identification of COX-2 inhibitors via in silico analysis' by Elagandhula Sathish et al., Org. Biomol. Chem., 2022, 20, 4746–4752, ; https://doi.org/10.1039/D2OB00467D .